The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/pon.5067
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing body image in posttreatment oral cavity cancer patients

Abstract: Objective: The purpose of this study of posttreatment oral cavity cancer (OCC) patients was to identify factors associated with self-reported overall body image, perceived attractiveness, and dissatisfaction with body appearance. Methods: This cross-sectional study recruited patients with OCC from the outpatient radiation department of a single cancer center in Northern Taiwan. Demographic and clinical characteristics were recorded, and patients were assessed using the Hospital Anxiety and Depression Scale (HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
(57 reference statements)
2
14
0
Order By: Relevance
“…More than four-fifths of our patients were of advanced stage and receiving multimodal treatments. These findings agree with those of previous studies of postoperative and chemotherapy patients [31,34]. These findings may reflect that an aspect of UGI organ resection resulted in patients who perceived alternation of body image due to changed appearance of their skin, disruption of soft tissue, or organ disfunction.…”
Section: Discussionsupporting
confidence: 91%
“…More than four-fifths of our patients were of advanced stage and receiving multimodal treatments. These findings agree with those of previous studies of postoperative and chemotherapy patients [31,34]. These findings may reflect that an aspect of UGI organ resection resulted in patients who perceived alternation of body image due to changed appearance of their skin, disruption of soft tissue, or organ disfunction.…”
Section: Discussionsupporting
confidence: 91%
“…Scores of 0 to 7 indicate the absence of depression, scores of 8 to 10 indicate borderline depression, and scores of 11 to 21 indicate clinical depression [25]. The scale was translated into Chinese, and a previous cancer-related study reported satisfactory psychometric properties for the HADS [26]. Cronbach's alpha for the HADS-Depression Subscale in the present study was 0.88.…”
Section: Hospital Anxiety and Depression Scale Depression Subscalesupporting
confidence: 49%
“…Scores of 0 to 7 indicate the absence of anxiety or depression; scores of 8 to 10 indicate borderline anxiety or depression; and scores of 11 to 21 indicate clinical anxiety or depression [ 30 ]. The scale was translated into Chinese, and a previous cancer-related study reported satisfactory psychometric properties for the HADS [ 31 ]. Cronbach’s alpha for the HADS-Anxiety Subscale and HADS-Depression Subscale in the present study was 0.90 and 0.88, respectively.…”
Section: Methodsmentioning
confidence: 99%